Gimkit-Based Learning Model on the Learning Outcomes of Akidah Akhlak of Class VIII Students of MTs Nurul Islam Sekarbela Mataram - Aisyah; Muhammad Bayu Lutfi (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
Student learning outcomes, particularly in the subject of Akidah Akhlak, need to be improved by applying more varied and non-monotonous learning models. One such model that can be implemented is the game-based learning model. The aim of this study is to determine the effect of the game-based learning model on the learning outcomes in Akidah Akhlak among eighth-grade students of MTs Nurul Islam Sekarbela Mataram in the 2024/2025 academic year. This research uses a quantitative approach with a quasi-experimental type. The research design employed is a pretest-posttest control-group design. The study was conducted by comparing two classes: a control class and an experimental class. The sample was selected using the cluster random sampling technique, with a total of 62 students in both the control and experimental groups. Data were collected using a multiple-choice test consisting of 25 questions. Final data analysis was performed using independent sample t-test at a significance level of 5% (0.05). Based on the results of the hypothesis test, the obtained significance value (2-tailed) was 0.009, which is smaller than 0.05 (0.009 < 0.05). This means that H ₁ is accepted and H ₀ is rejected, indicating that there is a significant effect of the game-based learning model on the Akidah Akhlak learning outcomes of eighth-grade students at MTs Nurul Islam Sekarbela Mataram in the 2024/2025 academic year.